2021
DOI: 10.1542/peds.2020-033704
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hospital Infant Safe Sleep Compliance by Using Safety Prevention Bundle Methodology

Abstract: BACKGROUND AND OBJECTIVES Sudden unexpected infant death often results from unsafe sleep environments and is the leading cause of postneonatal mortality in the United States. Standardization of infant sleep environment education has been revealed to impact such deaths. This standardized approach is similar to safety prevention bundles typically used to monitor and improve health outcomes, such as those related to hospital-acquired conditions (HACs). We sought to use the HAC model to measure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…Several prior studies have examined outcomes associated with implementing safe sleep initiatives in children’s hospitals. 5 , 18 21 A consistent area of statistically significant change among these studies, as with ours, is the reduction of nonmedical items in the crib, which is an essential behavior to model for families. 5 , 15 , 18 21 Although infants in our study were frequently asleep in the appropriate supine position in the preintervention group (86.5%), much like other studies, we failed to show improvement in this metric.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Several prior studies have examined outcomes associated with implementing safe sleep initiatives in children’s hospitals. 5 , 18 21 A consistent area of statistically significant change among these studies, as with ours, is the reduction of nonmedical items in the crib, which is an essential behavior to model for families. 5 , 15 , 18 21 Although infants in our study were frequently asleep in the appropriate supine position in the preintervention group (86.5%), much like other studies, we failed to show improvement in this metric.…”
Section: Discussionsupporting
confidence: 83%
“… 5 , 18 21 A consistent area of statistically significant change among these studies, as with ours, is the reduction of nonmedical items in the crib, which is an essential behavior to model for families. 5 , 15 , 18 21 Although infants in our study were frequently asleep in the appropriate supine position in the preintervention group (86.5%), much like other studies, we failed to show improvement in this metric. 5 , 18 , 19 , 21 Although prior quality improvement work demonstrated that hospital staff could remove medical supplies from hospital cribs, 5 we did not demonstrate improvement in that aspect of the sleep environment.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations